Specialty Collaboration in Managing School Age Child with Nasofrontal Meningoencephalocele: A Case Report - Salsabila, Yunia Tasya; Pribadi, Sweety; Hendriansyah, Lutfi; Pramono, Graciella Novian Triana Wahjoe (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2024)
Introduction : Meningoencephalocele is one form of neural tube defect that forms a sac containing brain tissue, meninges, and cerebrospinal fluid (CSF). It can cause structural deformities and many other clinical symptoms that come after. Many medical consultations are needed for the case. The collaboration between neurosurgeon and plastic surgeon plays a significant role in managing this case.Case Report : A case of a 10-year old boy with an apple-size lump in his nasofrontal region, nasal congestion, and central visual field disturbance. The patient has not undergone an examination or surgery in a long time because he lives in a rural area. Radiological results show herniaton brain tissue, meninges, and CSF protruding through the defect in the frontal bone of the cranium that suggest meningoencephalocele as a diagnosis.Discussion : The definitive management for this case is through surgery. Selecting a surgical technique for meningoencephalocele is essential for optimizing the outcomes and minimizing the risks. The Chula technique approach was chosen for the implementation of this surgery. In this case, we describe the modified Chula technique with stages adjusted according to the patient’s condition. Plastic surgery complements many aspects of reconstruction and restores aesthetic subunits. Managing this case was a challenge until the recovery period. The surgery was successfully performed, and patient went home without any serious complications.Summary: Caution is necessary in handling surgery and involves aesthetic creativity within it. Long-term monitoring is necessary for post-operative results since many clinical aspects and social developments must be regularly evaluated.